2007
DOI: 10.1111/j.1445-2197.2007.04267.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay to Surgery and Mortality After Hip Fracture

Abstract: Our study did not show a significant increase in mortality in patients whose surgery was delayed by more than 2 days. However, in the context of other published work, we would continue to recommend early surgery to minimize length of stay and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 12 publications
6
62
3
1
Order By: Relevance
“…Functional status before fracture, older age, male gender, and higher surgical risk increased the risk of mortality, whereas the use of antibiotics and physical therapy after surgery decreased the risk. Previous studies showed functional status before fracture [14,42,45,52], male gender [12,15,28,33,36,42,47], older age [10,15,28,36,43,47,50,52,55], and higher ASA scores predicted mortality in older patients [24,26,33,44,49] (Table 3), which is in agreement with our findings. In our study, we did not see a difference in mortality between patients undergoing arthroplasty versus patients undergoing osteosynthesis, which is in agreement with mortality reported by Garcia et al [15] and others [18,33,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Functional status before fracture, older age, male gender, and higher surgical risk increased the risk of mortality, whereas the use of antibiotics and physical therapy after surgery decreased the risk. Previous studies showed functional status before fracture [14,42,45,52], male gender [12,15,28,33,36,42,47], older age [10,15,28,36,43,47,50,52,55], and higher ASA scores predicted mortality in older patients [24,26,33,44,49] (Table 3), which is in agreement with our findings. In our study, we did not see a difference in mortality between patients undergoing arthroplasty versus patients undergoing osteosynthesis, which is in agreement with mortality reported by Garcia et al [15] and others [18,33,37].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies document comorbid diseases and prefracture health status are associated with the 1-year postfracture mortality [28,46,52], whereas others show no influence of these factors [10,55]. Studies from developed countries suggest preoperative factors increasing the risk of mortality are race (nonwhite) [27,42], old age [10,12,28,52], presence of dementia [24,42], male gender [12,24,33,42], serious concomitant illness [10,12,33,52], low body mass index (BMI) [24], low handgrip strength [37], not walking outdoors before fracture [37], history of hip fracture [4], delirium at admission [9], postoperative complications [46], high preoperative risk score [24,44], and postoperative mobility [25]. In developing countries, orthopaedic services are less available.…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de los trabajos reconocen que una cirugía "temprana" podría tener como punto de corte las primeras 48 horas e influye de una manera positiva en las tasas de mortalidad 15,20,22,[25][26][27][28][29][30][31][32] . Sin embargo, también hay autores que ponen en duda tal aseveración 14,23,33,34 . Existe controversia por tanto acerca de si el retraso en realizar la cirugía en este tipo de fracturas genera más mortalidad, pero lo que sí parece claro es que una cirugía temprana está asociada a un menor número de complicaciones, mejores resultados funcionales, menor estancia hospitalaria y menos reingresos, lo cual indudablemente está asociado a un menor coste 14,35 .…”
Section: Discussionunclassified
“…Sixteen of these citations proved eligible for inclusion 8,12,15,[22][23][24][25][26][27][28][29][30][31][32][33][34] (Figure 1). Two studies were possible duplicates, but we included both in our analysis because one assessed long-term mortality 24 and the other assessed shortterm mortality.…”
Section: Studies Includedmentioning
confidence: 99%